Respostas
respondido por:
0
Primeiro arrume a equação, tem que passar todos para um lado só e igualar a 0
2x² + x -1 = 0
∆ = b² - 4ac
∆ = (1)² - 4(2)(-1)
∆ = 1 + 8
∆ = 9
x = -b ± √∆ /2a
x = -(1) ± √9 /2(2)
x = -1 ± 9/4
x' = 8/4 = 2
x" = -10/4 = -5/2
2x² + x -1 = 0
∆ = b² - 4ac
∆ = (1)² - 4(2)(-1)
∆ = 1 + 8
∆ = 9
x = -b ± √∆ /2a
x = -(1) ± √9 /2(2)
x = -1 ± 9/4
x' = 8/4 = 2
x" = -10/4 = -5/2
respondido por:
0
Resposta:
x¹=-5 e x²=-1
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás